Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada J&T Express Drop Point Modang Tanah Grogot - Agus Budi Sadhono; Ibnu Khayath Farisanu; Boy Mansyah (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
The purpose of this study was to determine the effect of the variable Quality of Service which consists of Reliability (X1), Responsiveness (X2), Assurance (X3), Empathy (X4), Physical Evidence (X5) to influence simultaneously or partially on Consumer Satisfaction at J&T Express Drop Point Modang Tanah Grogot. The hypothesis in this study is that it is suspected that the service quality variables consisting of Reliability (X1), Responsiveness (X2), Assurance (X3), Empathy (X4), Physical Evidence (X5) have an effect on Consumer satisfaction (Y) at J&T Express Drop Point Modang Tanah Grogot. The results of the validity test of 26 questions, all have a value of rcount>rtable, which means that all questions are declared valid. Based on the results of the reliability test, the value of Cronbach's Alpha was obtained > 0.80 (0.949 > 0.80). So all questions are declared reliable. Based on the results of the analysis of the regression equation, Y = 33.126 + 0.239(X1) + 0.128(X2) + 0.185(X3) + 0.166(X4) + 0.207(X5) The correlation coefficient (R) is 0.899, which means that the correlation is very strong between service quality consisting of Reliability (X1), Responsiveness (X2), Assurance (X3), Empathy (X4), Physical Evidence (X5) with Consumer satisfaction (Y). While the value of the Coefficient of Determination (Adjusted R2) is 0.798, which means service quality (X) can explain consumer satisfaction (Y) at the J&T Express Drop Point Modang Tanah Grogot of 79.8% while the rest is explained by other factors not examined at (100 – 79 .8) % = 20.2%. The results of the simultaneous F test show that the quality of service influences simultaneously (together) on consumer satisfaction with Fcount > Ftable or states that Fcount is 79.174 > Ftable is 2.31 and the significance is 0.000 <0.05 so Ho is rejected and Ha is accepted. Partially the reliability variable (x1) has a partial effect on customer satisfaction (Y) with a count of 2.900 > ttable 1.98552, Responsiveness (X2) has no partial effect on customer satisfaction (Y) with tcount 1.617 < ttable 1.98552, warranty variable ( X3) has a partial effect on consumer satisfaction (Y) with tcount 2.202 > ttable 1.98552, Empathy (X4) has no partial effect on consumer satisfaction (Y) with tcount 1.904 < ttable 1.98552, ) physical evidence variable (x5) has a partial effect on consumer satisfaction (Y) with a calculation of 3.845 > ttable of 1.98552. So from these results it is known that the dominant variable is physical evidence (X5) because it has the largest tcount value of 3.845, then Ho is accepted and Ha is rejected.